Students’ and Applicants’ Social Perceptions of the Risks of Educational Environment at Higher Education Institution - A. V. Lyalyuk; O. R. Tuchina (Высшее образование в России)
Educational system is the most important social institution, which provides the development of a personality and frames his/her worldview and the conception of subjective well-being. Despite the large number of studies on the issue of psychological and pedagogical security of educational environment, the sphere of higher education still remains underexplored. The available empiric material has not received sufficient methodological justification and conceptualization. This article aims to provide the conceptualization of the risk category as applied to the educational environment of a higher education institution, as well as empiric investigation of the risks within the educational environment as viewed by applicants and students.Materials and methods. 213 applicants and 547 students of the Kuban State Technological University took part in the survey. The following investigation methods were used: expert assessment, interview, questioning, content analysis, analysis of means method, cluster analysis and factor analysis.Investigation results. Comparative examination of the manifestation degree of risks within the educational environment as viewed by applicants and students of higher education institution showed significant differences in the assessment of risk by these groups of respondents. From the point of view of applicants, the main risks are connected with social and psychological aspects of the educational environment of a higher education institution, relations within student groups and interaction with teachers, as well as with the issues related to the educational management and leisure arrangement. As viewed by the students, the risks within the educational environment include external and social and psychological risk factors, motivating risks and risks arising from the learning process organization and management and the related issues. Applicants’ notion of the risks within the educational environment of a higher education institution was mainly influenced by information they received from media and by the opinion of their relatives and age mates.Consideration and conclusions. It was proved that the applicants’ idea of the risks within the educational environment of a higher education institution is determined by the opinion of people they know personally, however it changes during the process of studying in higher education institution and acquiring their own experience of being within the environment. The investigation results allow creating a model of psychological and pedagogical security within the educational environment of a higher education institution. This model makes it possible to forecast main risks of the educational environment, their development, and evolvement and find solution to them.